ASPEK KOHESI KONJUNGSI DALAM WACANA OPINI PADA MAJALAH TEMPO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Sulis Setiawati (Universitas PGRI Sumatera Barat, 2015)
Opinion discourse that contained in a rubric of mass media can become an alternative media of bahasa Indonesia learning in schools, especially in opinion discourse material . One of the elements which need to be researched in opinion discourse is cohesion aspect. Cohesive subject of discourse can be determined by grammatical and lexical aspect. Grammatical cohesion aspect is characterized by the conjunction, ellipsis, substitution, and the reference. Lexical cohesion among other aspects of the reiteration and collocation. In order to get maximum results, these studies only focuses on one of grammatical cohesion aspect, i.e. conjunction aspect. Based on the analysis of the data that has been carried out, from 16 opinion discourse, there is 48 paragraph of samples with 95 pairs of adjacent obtained the result that 10 pairs were using grammatical cohesion in the form of the conjunction is around 10.5% and 85 pairs of adjacent sentences that not use the cohesion in the form of the conjunction is about 89,4%. However, it doesn’t mean that the adjecent pair is not cohesive in grammatical basis, considering there were still 3 other factors grammatical cohesion forming beside the conjunction, i.e., reference, substitution and ellipsis.